The residual effect of stylosanthes fodder banks on maize yield at several locations in Nigeria - Tarawali, G. (1991)
Investigates the response of maize to nitrogen on natural pasture (fallow), or following stylosanthes pastures (fodder banks) inside and outside fodder bank areas at 4 locations in central Nigeria. Maize planted in the fodder banks outyielded than on the natural fallow at each level of applied N.